2022
DOI: 10.3389/fcell.2022.813963
|View full text |Cite
|
Sign up to set email alerts
|

Review of LINC00707: A Novel LncRNA and Promising Biomarker for Human Diseases

Abstract: Long noncoding RNAs (lncRNAs) are a major type of noncoding RNA greater than 200 nucleotides in length involved in important regulatory processes. Abnormal expression of certain lncRNAs contributes to the pathogenesis of multiple diseases, including cancers. The lncRNA LINC00707 is located on chromosome 10p14 and is abnormally expressed in numerous disease types, and particularly in several types of cancer. High LINC00707 levels mediate a series of biological functions, including cell proliferation, apoptosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The target genes of significantly different lncRNA EN-90756 were mainly associated with Aberrant lncRNA expression is implicated in the pathogenesis of many diseases. Highly expressed lncRNA LINC00707 mediates a range of biological functions in humans, including cell proliferation, apoptosis, metastasis, invasion, cell cycle arrest, inflammation, and even osteogenic differentiation (Yao et al, 2022). In present study, the expression of lncRNA EN-90756 was significantly up-regulated with increasing treatment time of CPB2 toxin and reached its highest value at 24 h. EdU and cell viability assays showed that knockdown of lncRNA EN-90756 inhibited the proliferation of CPB2-treated IPEC-J2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The target genes of significantly different lncRNA EN-90756 were mainly associated with Aberrant lncRNA expression is implicated in the pathogenesis of many diseases. Highly expressed lncRNA LINC00707 mediates a range of biological functions in humans, including cell proliferation, apoptosis, metastasis, invasion, cell cycle arrest, inflammation, and even osteogenic differentiation (Yao et al, 2022). In present study, the expression of lncRNA EN-90756 was significantly up-regulated with increasing treatment time of CPB2 toxin and reached its highest value at 24 h. EdU and cell viability assays showed that knockdown of lncRNA EN-90756 inhibited the proliferation of CPB2-treated IPEC-J2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29]37 Uncontrolled cell proliferation is a major feature of cancer, and invasion and migration are important factors contributing to increased mortality from various cancers. 62,63 HCG18, as a ceRNA, is involved in regulating the proliferation, migration and invasion of GC cells. DNAJB12 is an Hsp40 family protein associated with the endoplasmic reticulum, DNAJB12 can be degraded under severe endoplasmic reticulum stress conditions and promote cancer cell apoptosis.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Uncontrolled cell proliferation is a major feature of cancer, and invasion and migration are important factors contributing to increased mortality from various cancers 62,63 . HCG18, as a ceRNA, is involved in regulating the proliferation, migration and invasion of GC cells.…”
Section: Hcg18 In Human Diseasementioning
confidence: 99%